The protein Z/protein Z-dependent protease inhibitor complex - Vasse, M. (Hämostaseologie, 2011)
Protein Z (PZ) is a vitamin K-dependent factor identified in human plasma in 1984 but it has no enzymatic activity. It is a cofactor of a serpin, the protein Z-dependent protease inhibitor (ZPI), and the complex PZ/ZPI inhibits activated factor X on phospholipid surfaces. In mice, the disruption of PZ or ZPI gene is asymptomatic, but enhances the thrombotic phenotype and mortality of other thrombotic risk factors. Most of the clinical studies focused on PZ. Despite conflicting results, a recent meta-analysis indicated that PZ deficiency could be a risk for venous and arterial thrombosis and early fetal loss. However, these conclusions are drawn from case-control studies of small size, constituting an important limitation. Recently, it was shown that PZ and/or ZPI are synthesised by normal kidney and different cancer cells, suggesting that the complex PZ/ZPI could play a role in inhibiting the tissue deposition of fibrin. The physiopathological consequences of these observations remain to be established. At this time, the measurement of plasma PZ and ZPI or analysis of their gene polymorphisms should not be performed routinely for the exploration of thrombophilia.
Keywords: Protein Z; protein Z-dependent protease inhibitor; thrombosis; cancer